Divalent cation‐aided identification of physico‐chemical properties of metal ions that stabilize RNA g‐quadruplexes. Issue 7 (July 2015) - Balaratnam, Sumirtha; Basu, Soumitra; Woodson, Sarah
ABSTRACT DNA and RNA sequences rich in guanosines (G) can form a four‐stranded secondary structure known as a G‐quadruplex (GQ), which plays a role in regulation of gene expression at the transcription and translation level. Both DNA and RNA GQs typically use the monovalent K+ ion for stabilization of the structures. However, the fundamental reasons for K+ acting as the most stabilizing metal ion for RNA GQs are not known. To identify the properties of a metal ion that stabilizes an RNA GQ we investigated the effect of alkaline earth metal cations and a set of divalent transition metal ions on two previously identified highly stable RNA GQs. Our results based upon circular dichroism and RNase T1 structure mapping data reveal that the RNA GQs are destabilized in the presence of the tested divalent metal cations. The destabilizing effect of a divalent metal cation is reversible upon increasing K+ concentration. Results show that ionic radius, hydration energy, and binding strength towards the hard ligand (guanine O6) are important factors that determine a metal ion's ability to stabilize an RNA GQ. Additionally, the tested set of divalent metal cations incongruously affects RNA and DNA GQs. © 2015 Wiley Periodicals, Inc. Biopolymers 103: 376–386, 2015.